2007
DOI: 10.1097/01.anes.0000270734.99298.b4
|View full text |Cite|
|
Sign up to set email alerts
|

Differential Dynamic of Action on Cortical and Subcortical Structures of Anesthetic Agents during Induction of Anesthesia

Abstract: These data suggest that in humans, unconsciousness mainly involves the cortical brain, but that suppression of movement in response to noxious stimuli is mediated through the effect of anesthetic agents on subcortical structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
124
1
8

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(143 citation statements)
references
References 55 publications
10
124
1
8
Order By: Relevance
“…Besides decreasing activity in the higher-order brain areas of the cortex, increase of connectivity has also been observed in other brain regions during sedation [66], as already observed in patients with DOC. Mild sedation with propofol increased thalamic excitability [65] and increased connectivity between the pontine tegmental area and the insulae [64].…”
Section: Unconsciousness In General Anesthesiasupporting
confidence: 65%
“…Besides decreasing activity in the higher-order brain areas of the cortex, increase of connectivity has also been observed in other brain regions during sedation [66], as already observed in patients with DOC. Mild sedation with propofol increased thalamic excitability [65] and increased connectivity between the pontine tegmental area and the insulae [64].…”
Section: Unconsciousness In General Anesthesiasupporting
confidence: 65%
“…Of notice, the opposite phenomenon (i.e., the cortex being deactivated before the thalamus) has been claimed recently to occur during anesthesia induction (33,34). This precedence in the decrease in thalamic activity is unlikely to be related to antiepileptic treatment or a patient's clinical condition.…”
Section: Discussionmentioning
confidence: 98%
“…Although thalamus is very likely involved in PI-LOC, observed changes in connectivity may be attributed to direct effects of propofol on thalamic nuclei or indirect effects via thalamocortical feedback loops. A study in Parkinson's patients reported that propofol-induction lead to slowing in cortical before subcortical electrophysiologic patterns, which may indicate a potentially secondary role of thalamus in initiating loss of consciousness (Velly et al, 2007). In contrast, for the onset of NREM sleep, deactivation of thalamus was found to precede that of cortex (Magnin et al, 2010).…”
Section: Effects Of Pi-loc On Subcortical and Cortical Functional Conmentioning
confidence: 99%